2014
DOI: 10.11604/pamj.2014.18.322.4440
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of methicillin resistant staphylococci strains isolated from surgical site infections in Kinshasa

Abstract: IntroductionSurgical site infections (SSIs) after surgery are usually caused by Staphylococcus aureus and coagulase-negative staphylococci (CNS). In low income countries, methicillin resistant Staphylococcus aureus (MRSA) and methicillin resistant coagulase-negative staphylococci (MR-CNS) surgical site infections are particularly associated with high treatment cost and remain a source of mortality and morbidity. This study aimed to determine the prevalence and the sensitivity to antibiotics of MRSA and MR-CNS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
5
19
0
Order By: Relevance
“…However the prevalence observed in this study was consistent with the reports from other parts of the world: 67.5% prevalence of MRCoNS was reported from blood cultures of septicaemia patients in Turkey (Ko Ksai et al, 2009) and 45% prevalence from surgical wounds (Rahman et al, 2013), 52% from a tertiary care hospital in Iran (Sharma et al, 2010). Iyamba et al, 2014 reported 60% prevalence of MRCoNS from surgical site infections from Kinshasa. The high prevalence of MRCoNS should be of great concern to health institutions and the community at large due to its antibiotics multi-resistance challenge and the financial burden on the in-patients especially here in Nigeria, a developing country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the prevalence observed in this study was consistent with the reports from other parts of the world: 67.5% prevalence of MRCoNS was reported from blood cultures of septicaemia patients in Turkey (Ko Ksai et al, 2009) and 45% prevalence from surgical wounds (Rahman et al, 2013), 52% from a tertiary care hospital in Iran (Sharma et al, 2010). Iyamba et al, 2014 reported 60% prevalence of MRCoNS from surgical site infections from Kinshasa. The high prevalence of MRCoNS should be of great concern to health institutions and the community at large due to its antibiotics multi-resistance challenge and the financial burden on the in-patients especially here in Nigeria, a developing country.…”
Section: Discussionmentioning
confidence: 99%
“…In a report by Diekema et al, 2001, resistance to penicillin among the coagulase-negative staphylococci (CoNS) approaches 90 to 95 percent, resistance to methicillin and semisynthetic penicillins has been observed in more than 80 percent of CoNS isolates; these isolates are often resistant to multiple classes of antibiotics in addition to beta-lactams, therefore limiting traditional treatment options, like those with semi-synthetic penicillins. Iyamba et al, 2014 reported high resistant of MRCoNS isolates to ampicillin (beta lactam), erythromycin (macrolide), clindamycin (lincosamine) and ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…82 Conversely, CoNS accounted for a high incidence of surgical site infections, following surgical procedures, when surgical site infections were characterized (Table 1). 6 Surgical site infections are infections affecting either the incision or deep tissue at the site of operation, and occurs up to 30 days postsurgery or up to 1 year in cases of those with implants. 6 Although improvements have been made in the prevention of postsurgical infections, surgical site infections remain problematic in surgical practice and account for increased cost of health care and prolonged hospitalization.…”
Section: Wound Infectionsmentioning
confidence: 99%
“…6 Surgical site infections are infections affecting either the incision or deep tissue at the site of operation, and occurs up to 30 days postsurgery or up to 1 year in cases of those with implants. 6 Although improvements have been made in the prevention of postsurgical infections, surgical site infections remain problematic in surgical practice and account for increased cost of health care and prolonged hospitalization. 83 Studies show that most of the causes of surgical site infections are normal residents of the skin, such as CoNS and S. aureus.…”
Section: Wound Infectionsmentioning
confidence: 99%
See 1 more Smart Citation